Bacterial synovitis: An unusual pathogen (Indian Journal of Case Reports, 2026)
A 40-year-old male patient presented with pain and swelling in both knee joints for 2 months. On examination and investigation, the patient was diagnosed with suspected acute synovitis, and arthrotomy with synovectomy was performed. The patient’s condition worsened with fever, collection of fluid in the joint, and an increase in blood leukocyte count. Upon performing culture and identification by an automated system, Staphylococcus haemolyticus was isolated, which was sensitive to doxycycline and vancomycin but resistant to linezolid. The patient was initiated on intravenous Vancomycin at a dosage of 1 g every 12 hours. The regimen was continued for a total duration of 7 days, after which the patient demonstrated complete clinical recovery.